Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Kognitif dan Sikap Ilmiah Siswa SMA pada Materi Termokimia - Nurhaliza Adisha; Eli Rohaeti (Postgraduate, University of Mataram, 2024)
This study seeks to ascertain whether there are notable disparities in cognitive learning outcomes and scientific attitudes among high school students in both the experimental and control groups regarding thermochemical topics. Additionally, it aims to outline the cognitive learning outcomes profile in the experimental group and evaluate the scientific attitude profile of students in the same group concerning thermochemical concepts. This research is using quantitative research method. The population in this study were five high schools in Sleman Regency, Ngaglik Region. The sample used was SMA 2 Ngaglik in class XI Science. The research employed both non-test methods, such as questionnaires, and test-based approaches, using multiple-choice questions, for data collection. Non-parametric analysis was utilized for data analysis. The findings indicated that there were no significant variances in cognitive learning achievements and scientific attitudes among high school students in both the experimental and control groups regarding thermochemical topics. Moreover, the learning outcomes profile in classes implementing the Problem Based Learning model and scientific approach was rated as very good, while the scientific attitude profile in these classes was deemed adequate across all aspects